2020
DOI: 10.1186/s12576-020-00744-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding vestibular-related physiological functions could provide clues on adapting to a new gravitational environment

Abstract: The peripheral vestibular organs are sensors for linear acceleration (gravity and head tilt) and rotation. Further, they regulate various body functions, including body stability, ocular movement, autonomic nerve activity, arterial pressure, body temperature, and muscle and bone metabolism. The gravitational environment influences these functions given the highly plastic responsiveness of the vestibular system. This review demonstrates that hypergravity or microgravity induces changes in vestibular-related phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 89 publications
(129 reference statements)
0
12
0
Order By: Relevance
“…In rats, after 90 min of exposure to 2 g , the immunoreactivity of CRH in PVN was significantly increased, but in VL it was weakened 26 and ACTH (adrenocorticotropic hormone) and corticosterone concentrations in plasma increased significantly against 1 g control 26 . From these, CRH-producing neurons in PVN may receive neuronal inputs from the vestibular system 27 . In addition, the centrifugal environment was stressful for mice because Fos was observed in PVN 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In rats, after 90 min of exposure to 2 g , the immunoreactivity of CRH in PVN was significantly increased, but in VL it was weakened 26 and ACTH (adrenocorticotropic hormone) and corticosterone concentrations in plasma increased significantly against 1 g control 26 . From these, CRH-producing neurons in PVN may receive neuronal inputs from the vestibular system 27 . In addition, the centrifugal environment was stressful for mice because Fos was observed in PVN 26 .…”
Section: Resultsmentioning
confidence: 99%
“…A study on the behavior of MG mice aboard the ISS for around 3 days showed a high activity ratio in the case of group rearing in a microgravity environment 7 . The vestibular system controls a variety of physical functions such as physical stability, sympathetic nerve activity, arterial pressure, feeding behavior, body temperature, and muscle and bone metabolism 27 . However, it is very plastic, and its function changes when exposed to various gravitational environments 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies observed the alternations of gene and miRNA expression under gravity changing, but the mechanisms remained to be addressed. As we know, the vestibular organs are sensors for gravity changes in vivo [ 59 ], but the mechanism about “how cells in vitro detect the gravitational changes” are still unclear. There were some hypotheses about it.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation, microgravity, altered atmospheric gas composition, isolation, and diet changes are some of the known stressors on humans in the space environment; these factors are expected to increase with mission duration and distance outside of low Earth orbit. 1 , 2 Examples of adverse human health effects during spaceflight include bone demineralization, 3 skeletal muscle atrophy, 4 cardiovascular deconditioning, 5 vestibular control, 6 immune system suppression, 7 , 8 and neuro-ocular ailments. 9 It is necessary to better understand how spaceflight factors affect human health in order to develop the countermeasures needed for safe and effective crewed space missions.…”
Section: Introductionmentioning
confidence: 99%